Pentingnya Pendidikan Multikultur Dalam Pembelajaran di Sekolah Dasar - I Gede Dharman Gunawan (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
Learning that is carried out in elementary schools is very important in providing multicultural education for students. Primary school is the starting place for students to study. In the learning process in schools that is followed by students from various backgrounds, it is felt that multicultural education is very important. Multicultural education in learning requires an introduction to the various cultures possessed by humans from various ethnic groups, races or ethnicities, and religions. With the existence of differences in ethnicity, race, and religion in learning in elementary schools, a learning process is needed to be able to teach multicultural education with shared values. The value of togetherness in learning in elementary schools such as learning to live in diversity, building mutual trust between students, maintaining mutual understanding, and upholding mutual respect.